2008
DOI: 10.1080/09674845.2008.11732788
|View full text |Cite
|
Sign up to set email alerts
|

Methicillin-resistant Staphylococcus aureus detection using chromogenic media: the Sheffield experience

Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) continues to cause major problems, both in hospitals and the community. Microbiology departments need to review their methodology regularly to ensure that they are contributing in the most appropriate manner to the battle against MRSA. Media employing chromogenic enzymes to aid the isolation and identification of MRSA is a relatively new approach. In this study, 192 swabs from 112 different patients were inoculated on two chromogen-containing media and four ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Antibiotic resistance continues to be a major international problem in clinical microbiology, as reflected by the high frequency of scientific research into this topic [38][39][40][41][42][43][44][45]. Although group B Streptococcus species are widely believed to be sensitive to penicillin, a screening method for the possibility of reduced sensitivity (i.e., resistance) has been developed [46].…”
Section: Microbiologymentioning
confidence: 99%
“…Antibiotic resistance continues to be a major international problem in clinical microbiology, as reflected by the high frequency of scientific research into this topic [38][39][40][41][42][43][44][45]. Although group B Streptococcus species are widely believed to be sensitive to penicillin, a screening method for the possibility of reduced sensitivity (i.e., resistance) has been developed [46].…”
Section: Microbiologymentioning
confidence: 99%
“…Overall, 192 swabs from wounds, nares, perineum/groin, eye, axilla, and throat were evaluated, with a positivity rate of 53.1% (62 swabs were taken from previously evaluated specimens known to be positive for MRSA) (4). Both chromogenic media had sensitivities of 96% by 48 h, although the extended incubation time did result in some false positives (4). The second study, by Pape et al, found BBL CHROMagar MRSA to be 100% sensitive and specific at 48 h for the isolation of MRSA from 124 positive blood cultures (13).…”
Section: Discussionmentioning
confidence: 99%
“…Nearly all studies that have evaluated chromogenic media for the detection of MRSA have used surveillance specimens, predominantly from the nares but also including specimens from axilla, groin, rectum, perineum, throat, and wounds (1-3, 7, 8, 10-12, 14, 15), and several studies have found additional reservoirs of MRSA by comparing alternate anatomical sites (1,2,7,11). Comparatively, there have only been two studies that have evaluated the use of chromogenic media for the isolation of MRSA from nonsurveillance clinical specimens (4,13). A British study by Davies et al compared two chromogenic media, MRSASelect agar (Bio-Rad) and CHROMagar MRSA (BioConnections), with four other, nonchromogenic formulations for MRSA detection (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation